2003
DOI: 10.1136/jmg.40.8.640
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evidence of heterogeneity in intrahepatic cholestasis of pregnancy

Abstract: Background and aims:The aim of this study was to investigate the genetic aetiology of intrahepatic cholestasis of pregnancy (ICP) and the impact of known cholestasis genes (BSEP, FIC1, and MDR3) on the development of this disease. Patients and methods: Sixty nine Finnish ICP patients were prospectively interviewed for a family history of ICP, and clinical features were compared in patients with familial ICP (patients with a positive family history, n=11) and sporadic patients (patients with no known family his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
73
0
5

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(80 citation statements)
references
References 23 publications
2
73
0
5
Order By: Relevance
“…ICP has been described in heterozygous mothers of affected children with PFIC. 20 Implicating family screening, 40% of the patients of PFIC had an affected sibling or family member. Previous studies 17,18 have reported affected sibling in 15-25% of PFIC.…”
Section: Discussionmentioning
confidence: 99%
“…ICP has been described in heterozygous mothers of affected children with PFIC. 20 Implicating family screening, 40% of the patients of PFIC had an affected sibling or family member. Previous studies 17,18 have reported affected sibling in 15-25% of PFIC.…”
Section: Discussionmentioning
confidence: 99%
“…9 Avrupa'da, en sık İskandinav ülkelerinde (İsveç'te %1,5) olmakla beraber %0,1-0,2 sıklığında izlenmektedir. 3 Son zamanlarda Şili'de GİK'nin insidansının azaldığı (%1,4-4,0) rapor edilmiştir. 13,14 Aynı zaman diliminde İskandinavya'da da prevalansın %0,1-1,5 değerlerine düştüğü rapor edilmiştir.…”
Section: Epi̇demi̇yoloji̇unclassified
“…1 Hastalık, coğrafi konum ve etnik orijine göre %0,1-15,6 arasında değişen sık-lıkla görülmektedir. [2][3][4][5] Gebelikte viral hepatit tanısından sonra en sık görülen sarılık sebebidir. 6 Özellikle gebeliğin ikinci yarısından sonra maternal kanda artmış safra asit düzeyleri ve bozulmuş karaciğer fonksiyon testleri (KFT) ile seyretmektedir.…”
unclassified
“…1,2 In Scandinavian countries, ICP occurs in 0.5 -1.5% of pregnancies. 3,4 The genetic etiology of ICP is largely unknown, and likely to be heterogenous. Currently, investigation of the genetic background of ICP is focused mainly on candidate genes, particularly those causing cholestatic diseases.…”
Section: Introductionmentioning
confidence: 99%